Vitamin D Status of Healthy School Children from Western Saudi Arabia - Kensarah, Osama Adnan; Azzeh, Firas Sultan (Pakistan Journal of Nutrition, 2012)
This study was conducted to evaluate vitamin D in healthy school children from Makkah area. A total of 148 healthy school children (87 boys and 61 girls) were included in this study. Vitamin D as 25-hydroxyvitamin D [25 (OH)-D] was measured as indication of vitamin D status. Serum 25 (OH)-D less than 20 ng/ml was considered as vitamin D deficient subject. Other biochemical indicators were also measured as calcium, phosphorus, alkaline phosphatase and parathyroid hormone. The mean age of the subjects was 10.1 years. Overall serum vitamin D was 10.5 ng/ml, which was significantly higher in male group than female. About 96.7% and 78.2% of females and males were deficient in vitamin D, respectively. No sufficient vitamin D female subject was recognized. The prevalence of vitamin D deficiency in children school from Makkah was very high and the deficiency was higher in females than males. The main reason for vitamin D deficiency was the restriction to sunlight exposure.